Soil dynamics and carbon stocks 10 years after restoration of degraded land using Atlantic Forest tree species - Rodrigues Nogueira, L. Jr.; de Moraes Gonçalves, J.L.; Lex Engel, V.; Parrotta, J. (Forest Systems, 2011)
Brazil’s Atlantic Forest ecosystem has been greatly affected by land use changes, with only 11.26% of its original vegetation cover remaining. Currently, Atlantic Forest restoration is receiving increasing attention because of its potential for carbon sequestration and the important role of soil carbon in the global carbon balance. Soil organic matter is also essential for physical, chemical and biological components of soil fertility and forest sustainability. This study evaluated the potential for soil recovery in contrasting restoration models using indigenous Atlantic Forest tree species ten years after their establishment. The study site is located in Botucatu municipality, São Paulo State-Brazil, in a loamy dystrophic Red-Yellow Argisol site (Typic Hapludult). Four treatments were compared: i) Control (Spontaneous Restoration); ii) Low Diversity (five fast-growing tree species established by direct seeding); iii) High Diversity (mixed plantings of 41 species established with seedlings) and; iv) Native Forest (well conserved neighboring forest fragment). The following soil properties were evaluated: (1) physical- texture, density and porosity; (2) chemical- C, N, P, S, K, Ca, Mg, Al and pH; (3) biological-microbial biomass. Litter nutrient concentrations (P, S, K, Ca and Mg) and C and N litter stocks were determined. Within ten years the litter C and N stocks of the Low Diversity treatment area were higher than Control and similar to those in both the High Diversity treatment and the Native Forest. Soil C stocks increased through time for both models and in the Control plots, but remained highest in the Native Forest. The methods of restoration were shown to have different effects on soil dynamics, mainly on chemical properties. These results show that, at least in the short-term, changes in soil properties are more rapid in a less complex system like the Low Diversity model than in the a High Species Diversity model. For both mixed plantation systems, carbon soil cycling can be reestablished, resulting in increases in carbon stocks in both soil and litter.